Word association technique to strengthen in EFL students vocabulary acquisition - Amador Amador, Blanca Luisa | Carbonero Rosales, Stephanny | Jarquín Cabrera, Alexa Wualquiria | Alemán Quintanilla, Jaime Roberto Alemán Quintanilla Jaime Roberto (UNAN, Managua, 2021)
This study aims to analyze whether word association is an excellent technique to improve vocabulary acquisition, in 9th “A “grade, at Rosa Cerda Amador Institute in Boaco, second semester 2020 in the morning shift. Participants involved are 43 high school students. The data collection instruments consisted of a guide observation, and Quasi experiment. The purposes of these instruments were to analyze between two groups of students whether word association is an excellent technique to acquire new vocabulary which consist in a pre-test. Groups of 20 students were taken to be evaluated to find out the previous knowledge they have and the post-test in which one group of 10 students will be exposed to the word association technique to acquire vocabulary and the other group of 10 students without having been exposed to the word association. It was noticed that most of the students do not have a wide knowledge of vocabulary. Finally, some recommendations were given to the teacher and students in order to strengthen learning and teaching in the acquisition of new vocabulary through the word association technique